Does Inbound Tourism Encourage Trade Deficit in Sri Lanka? - Bhavan, Thangamani (Asian Development Policy Review, 2019)
The purpose of this paper is to investigate whether tourism encourages imports and subsequently leading to a trade deficit, as the nexus between trade and tourism has been controversial. Annual time-series data, running from 1970 to 2017, are employed for the empirical analysis. The Augmented Dickey-Fuller (ADF) unit root analysis is used to test the stationary properties of the time series variables. The time series properties of the variables allowed employing the Johansen’s maximum likelihood estimator of the parameters of a cointegrating Vector Error Correction Model (VECM) analysis to inspect the long-run and the short-run dynamic relationship. The bilateral causality relationships between variables are tested by using the Granger Causality analysis. The results suggest the existence of a long-run relationship between tourism-related variables. Further, the results also confirm the causality running from inbound tourism to imports of goods and services, but not from import to tourism. However, there is no short-run dynamic relationship found to have between the variables.